Beyond mono fertilization: Mixed fertilization enhances productivity and quality of chili (Capsicum frutescens) - Hossain Md Dalim; Md Golam Jilani Helal; Minhazul Kashem Chowdhury; Shoaib Rahman; Sohel Rana Mazumder; Md. Ismail Hossain; Md. Mohi Uddin Sujan Chowdury; Md. Shahariar Jaman (PLoS ONE, 2026)
While the effects of different fertilization strategies on chili ( Capsicum frutescens ) cultivation have been previously examined, the lack of comparative assessment of mixed versus mono-fertilization approaches limits our understanding. To address this gap, we conducted an experiment using a completely randomized design (CRD) with five fertilization treatments along with four replications of each treatment (e.g., Leucaena leucocephala leaf litter and recommended dose of synthetic fertilizers (RDF)) to observe the effect of these treatments on productivity traits, NPP (net primary productivity), quality, and overall yield of chili. We found that mixed fertilization (T 4 ) results higher yield (~ 60% and ~ 90%) compared to control (T 0 ) and sole organic fertilizer (T 1 + T 2 ) respectively. The T 4 treatment showed consistently higher plant height, leaf and fruit number at 60 DAT, as well as higher flowering at 45 DAT compared to other treatments. We also found that NPP (above- and belowground combined) was higher in T 3 and T₄ treatments compared to control and organic fertilization. Similarly, quality traits such as vitamin C, capsaicin content, and SPAD reading were higher under mixed fertilization. Linear fit regression model indicated that both ANPP and yield were positively associated with vegetative and reproductive traits, particularly leaf number and flowering, highlighting that structural growth directly contributed to productivity gains. Overall, our results suggest that mixed fertilization enhances both productivity and quality traits of chili. Therefore, integrated organic and inorganic fertilizer management are recommended to improve yield and quality of chili.